Continuous Finite Element Methods of Molecular Dynamics Simulations - Qiong Tang; Luohua Liu; Yujun Zheng (Modelling and Simulation in Engineering)
Molecular dynamics simulations are necessary to perform very long integration times. In this paper, we discuss continuous finite element methods for molecular dynamics simulation problems. Our numerical results about AB diatomic molecular system and A2B triatomic molecules show that linear finite element and quadratic finite element methods can better preserve the motion characteristics of molecular dynamics, that is, properties of energy conservation and long-term stability. So finite element method is also a reliable method to simulate long-time classical trajectory of molecular systems.